Implementasi Akuntansi dalam Perspektif Pedagang Suku Jawa - Tresnawati, Sri Nanda; Rahayu, Ruci Arizanda (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to find out how Javanese traders practice accounting in managing their business. The application of accounting referred to in this study is budgeting, recording and determining the selling price of merchandise. This research was conducted at Pohjejer Market using qualitative methods with a phenomenological approach. The results of the study show that Javanese traders in Pohjejer Market do not apply budgeting and record-keeping accounting. Apart from that, in its application it is still influenced by the local wisdom of Javanese culture, such as determining the selling price which not only provides material benefits but also non-material benefits. This research has implications for Javanese traders who sell in traditional markets so that they can record business funds systematically. With systematic recording, traders can make decisions for the progress of their business.